Tumor secretome shapes the immune landscape during cancer progression - Jianqiang Yang; Sijia Tang; Nabil F. Saba; Chloe Shay; Yong Teng (Journal of Experimental & Clinical Cancer Research)
Abstract The focus of cancer immunotherapy has traditionally been on immune cells and tumor cells themselves, often overlooking the tumor secretome. This review provides a comprehensive overview of the intricate relationship between tumor cells and the immune response in cancer progression. It highlights the pivotal role of the tumor secretome - a diverse set of molecules secreted by tumor cells - in significantly influencing immune modulation, promoting immunosuppression, and facilitating tumor survival. In addition to elucidating these complex interactions, this review discusses current clinical trials targeting the tumor secretome and highlights their potential to advance personalized medicine strategies. These trials aim to overcome the challenges of the tumor microenvironment by designing therapies tailored to the secretome profiles of individual cancer patients. In addition, advances in proteomic techniques are highlighted as essential tools for unraveling the complexity of the tumor secretome, paving the way for improved cancer treatment outcomes.